2015
DOI: 10.1371/journal.pone.0141657
|View full text |Cite
|
Sign up to set email alerts
|

Transactivation of ErbB Family of Receptor Tyrosine Kinases Is Inhibited by Angiotensin-(1-7) via Its Mas Receptor

Abstract: Transactivation of the epidermal growth factor receptor (EGFR or ErbB) family members, namely EGFR and ErbB2, appears important in the development of diabetes-induced vascular dysfunction. Angiotensin-(1–7) [Ang-(1–7)] can prevent the development of hyperglycemia-induced vascular complications partly through inhibiting EGFR transactivation. Here, we investigated whether Ang-(1–7) can inhibit transactivation of ErbB2 as well as other ErbB receptors in vivo and in vitro. Streptozotocin-induced diabetic rats were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 48 publications
4
47
0
Order By: Relevance
“…23 Furthermore, recent evidence suggests that signaling through Mas1 can inhibit AT1R-dependent transactivation of epidermal growth factor receptor. 24 However, whether inhibition of this pathway plays a role in Ang 1-7-dependent inhibition of receptor activated aldosterone secretion remains to be directly studied.…”
Section: Discussionmentioning
confidence: 99%
“…23 Furthermore, recent evidence suggests that signaling through Mas1 can inhibit AT1R-dependent transactivation of epidermal growth factor receptor. 24 However, whether inhibition of this pathway plays a role in Ang 1-7-dependent inhibition of receptor activated aldosterone secretion remains to be directly studied.…”
Section: Discussionmentioning
confidence: 99%
“…In cultured vascular smooth muscle cells, Ang II and glucose induce the transactivation of EGFR, however, this transactivation is attenuated by angitensin-(1–7) via the activation of Mas receptor [ 77 ]. They later showed that Ang-(1–7) acts as a pan-ErbB inhibitor via its Mas receptor [ 78 ]. It is well established that GPCR transactivates EGFR through Src, this is the first report that GPCR/Src pathway is involved in the inhibition of EGFR transactivation by other GPCRs.…”
Section: Progress In the Last Five Yearsmentioning
confidence: 99%
“…We have shown that activation of this beneficial pathway endogenously or exogenously by administering Ang-(1-7) or its analog prevents or improves the multiple diabetes-induced complications [21,34,37,[125][126][127] including some through inhibiting the transactivation of EGFR/ErbB receptors [128,129]. In models of diabetes and/or hypertension, we have shown that administering Ang-(1-7) prevented endothelial dysfunction, cardiac and renal end-organ damage via mechanisms involving inhibition of NADPH oxidase, NF-kB, TLR-2, IRAK-1, IL-6, EGFR receptors, and renal TGF-beta [32,40,128,129] or activation of NO, catalase and PPAR-gamma pathways [34,130]. It should be noted here, that activation of ACE2-Ang-(1-7) pathway has little or no effects on normal/healthy animals but displays its beneficial anti-pressor effects or cardiovascular benefits only in models of disease e.g.…”
Section: Meta-analyses Of Clinical Studies Of Covid-19 Patients Receimentioning
confidence: 99%